Modified clay-based material, preparation method thereof and application of modified clay-based material as adsorbent
Through the application of modified clay-based materials, the problem of removing methyl chloride silane impurities in polycrystalline silicon production is solved, efficient adsorption effect and cost reduction are achieved, and the purity and production efficiency of polycrystalline silicon are improved.
Patent Information
- Application Number
- CN202411287006.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
In the existing polycrystalline silicon production processes, distillation technology is difficult to effectively remove methyl chloride silane impurities in trichlorosilane, especially monomethyl dichlorosilane, resulting in low separation efficiency, high cost and high energy consumption.
By introducing a modifier, the adsorption sites and defect sites on its micropores and surface are increased to form a modified clay-based material with high adsorption properties for adsorption of methylchlorosilane impurities.
Highly efficient adsorption of methylchlorosilane impurities, especially the adsorption removal rate of monomethyldichlorosilane is achieved, which simplifies production steps and reduces costs while improving the stability of the material.
Smart Images

Figure CN119140077A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polysilicon production, and in particular to a modified clay-based material and a preparation method thereof and an application thereof as an adsorbent. Background Art
[0002] With the increasing depletion of primary energy and the gradual warming of the climate, green energy such as photovoltaics and wind power will be the mainstream of future development. In the photovoltaic industry, the photoelectric conversion efficiency of solar cells is a key factor affecting the cost of photovoltaic power generation, and carbon impurities in polysilicon raw materials have an adverse effect on the photoelectric conversion efficiency of solar cells.
[0003] As an important raw material for the preparation of polysilicon, trichlorosilane is one of the main sources of carbon impurities in polysilicon. Trichlorosilane contains methylchlorosilane impurities, including monomethyldichlorosilane and monomethyltrichlorosilane, among which the removal of monomethyldichlorosilane is more difficult than that of monomethyltrichlorosilane. Therefore, purifying trichlorosilane and removing the methylchlorosilane impurities contained therein, especially the monomethyldichlorosilane impurities, is one of the important problems facing the polysilicon industry. In the prior art, the production process of polysilicon mainly adopts the modified Siemens method, which first produces crude trichlorosilane, and then purifies trichlorosilane through multi-stage distillation technology to obtain refined trichlorosilane. However, since the boiling point of methylchlorosilane impurities is close to that of trichlorosilane, conventional distillation processes are not only difficult to remove methylchlorosilane impurities, but also lead to higher energy consumption. Therefore, in view of the problems of low separation efficiency, high cost, high energy consumption and complicated process in distillation technology, finding a simpler and more effective method for removing carbon impurities is the focus in polysilicon production. Studies have shown that catalytic reaction technology and adsorption technology can effectively remove methylchlorosilane impurities. Among them, due to the influence of the concentration of methylchlorosilane impurities in trichlorosilane, the application of catalytic reaction technology in the further purification of high-purity trichlorosilane is limited. Compared with the catalytic reaction method, the adsorption method can improve its selective adsorption capacity by adjusting factors such as the pore size range and the type of active groups of the adsorbent, thereby further enhancing the purification effect.
[0004] Therefore, how to develop an adsorbent with high selectivity for methylchlorosilane impurities, especially monomethyldichlorosilane impurities, is of great significance for improving the purity of trichlorosilane and polysilicon, simplifying the production steps, and reducing the production cost. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a modified clay-based material and a preparation method thereof and an application thereof as an adsorbent.
[0006] In order to achieve the above object, the present invention provides a modified clay-based material on one hand, wherein the modified clay-based material is obtained by modifying the clay-based material with a modifier, wherein the modifier is selected from one or more structures represented by formula I, formula II and formula III.
[0007]
[0008] wherein A and B are each independently selected from one or more of C1-C12 alkylene and C1-C12 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C12 alkyl, C1-C12 carboxyl, C2-C12 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C12 alkyl, C1-C12 aminoalkyl and C6-C12 aryl, and X - Selected from salt-forming anions.
[0009] A second aspect of the present invention provides a method for preparing a modified clay-based material, the method comprising:
[0010] (1) contacting and reacting a modifier with a clay-based material to obtain a clay-based modified precursor;
[0011] (2) calcining the clay-based modified precursor to obtain a modified clay-based material;
[0012] Wherein, the modifier is selected from one or more structures represented by formula I, formula II and formula III,
[0013]
[0014] wherein A and B are each independently selected from one or more of C1-C12 alkylene and C1-C12 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C12 alkyl, C1-C12 carboxyl, C2-C12 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C12 alkyl, C1-C12 aminoalkyl and C6-C12 aryl, and X - Selected from salt-forming anions.
[0015] The third aspect of the present invention provides a modified clay-based material obtained by the above method.
[0016] A fourth aspect of the present invention provides a use of the modified clay-based material as an adsorbent.
[0017] A fifth aspect of the present invention provides a use of the modified clay-based material as an adsorbent for removing methylchlorosilane impurities in polysilicon production.
[0018] The present invention introduces a modified group provided by a specific modifier into a clay-based material through a specific modifier, thereby increasing the adsorption sites, defect sites and electron cloud density of the micropores and surface of the clay-based material, enhancing its induced polarization ability, and obtaining a modified clay-based material with good performance. The modified clay-based material has excellent adsorption performance, has excellent adsorption efficiency and catalytic conversion ability for methylchlorosilane impurities (especially monomethyldichlorosilane), and has a simple preparation process, low cost and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the thermal gravimetric curve of the modified halloysite nanotubes prepared in Example 1;
[0020] Figure 2 The nitrogen adsorption curves of the adsorbents prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] In the present invention, each group is independently selected from means that they are independently selected and may be the same or different.
[0023] In one aspect, the present invention provides a modified clay-based material, wherein the modified clay-based material is obtained by modifying a clay-based material with a modifier, wherein the modifier is selected from one or more structures represented by formula I, formula II and formula III.
[0024]
[0025] wherein A and B are each independently selected from one or more of C1-C12 alkylene and C1-C12 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C12 alkyl, C1-C12 carboxyl, C2-C12 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C12 alkyl, C1-C12 aminoalkyl and C6-C12 aryl, and X - Selected from salt-forming anions.
[0026] According to the present invention, in order to further increase the adsorption sites and defect sites on the surface of the modified clay-based material, preferably, A and B are each independently selected from one or more of C1-C6 alkylene and C1-C6 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C6 alkyl, C1-C6 carboxyl, C2-C6 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C6 alkyl, C1-C6 aminoalkyl and C6-C12 aryl, X - Selected from Cl - Br - ,I - 、CH3COO - 、NO3 - 、HSO4 - 、H2PO4 - 、BF4 - and SbF6 - One or more of .
[0027] More preferably, A and B are each independently selected from one or more of methylene, ethylene, n-propylene, n-butylene, n-pentylene, n-hexylene, -NHCH2CH2-, -CH2NHCH2-, -NHCH2CH2CH2-, -CH2NHCH2CH2-, -NHCH2CH2CH2CH2-, -NH(CH3)CH2CH2CH2-, -CH2NHCH2CH2CH2-, -CH2CH2NHCH2CH2- and -NHCH2CH2CH2CH2CH2-, and R1, R2, R3 and R4 are each independently selected from methyl, ethyl, n-propyl, isopropyl R5, R6, R7 and R8 are each independently selected from one or more of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, carboxymethyl, carboxyethyl, n-carboxypropyl, n-carboxybutyl, n-carboxypentyl, vinyl, allyl, 1-butenyl, 2-butenyl, phenyl, benzyl, p-methylphenyl, p-ethylphenyl, p-n-propylphenyl and naphthyl, R5, R6, R7 and R8 are each independently selected from one or more of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, aminomethyl, aminoethyl, n-aminopropyl, isoaminopropyl, n-aminobutyl, isoaminobutyl, n-aminopentyl, n-aminohexyl, phenyl, benzyl, p-methylphenyl, p-ethylphenyl, p-n-propylphenyl and naphthyl, X - Selected from Cl - Br - and I - One or more of .
[0028] In a preferred embodiment of the present invention, the modifier satisfies: In Formula I, A is selected from one or more C1-C12 alkylene groups, B is selected from one or more C1-C12 alkylene groups and C1-C12 aminoalkylene groups. In Formula II, at least one of R1, R2, R3 and R4 is selected from one or more C6-C12 aryl groups, and X - Selected from Cl - Br - and I - In formula III, at least one of R5, R6, R7 and R8 is selected from one or more of C1-C12 alkyl groups.
[0029] More preferably, in Formula I, A is selected from one or more C1-C6 alkylene groups, and B is selected from one or more C1-C6 alkylene groups and C1-C6 aminoalkylene groups. In Formula II, at least one of R1, R2, R3 and R4 is selected from one or more C6-C12 aryl groups, and X - Selected from Cl - Br - and I - In formula III, at least one of R5, R6, R7 and R8 is selected from one or more of C1-C6 alkyl groups.
[0030] More preferably, in Formula I, A is selected from one or more of n-propylene, n-butylene and n-pentylene, and B is selected from one or more of n-propylene, n-butylene, n-pentylene, -NHCH2CH2CH2-, -CH2NHCH2CH2-, -NH(CH3)CH2CH2CH2- and -CH2NHCH2CH2CH2-. In Formula II, at least one of R1, R2, R3 and R4 is selected from one or more of phenyl, benzyl and p-methylphenyl, and X - Selected from Cl - Br - and I - In formula III, at least one of R5, R6, R7 and R8 is selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl and n-hexyl.
[0031] According to a particularly preferred embodiment of the present invention, the modifier is selected from one or more compounds represented by the following structures:
[0032]
[0033] On the basis of the above particularly preferred embodiments, further preferably, the modifier can be selected from one or more compounds represented by the following structures:
[0034]
[0035] According to the present invention, in order to further enhance the adsorption activity and catalytic conversion ability of the modified clay-based material, preferably, the content of the modified group provided by the modifier in the modified clay-based material is 0.5-30wt%, preferably 5-20wt%, for example, it can be 6wt%, 9wt%, 12wt% and 18wt% and any range between them. Preferably, the mesoporous volume of the modified clay-based material is 0.05-0.5cm 3 / g, preferably 0.15-0.25cm 3 / g, for example, 0.15 cm 3 / g, 0.17cm 3 / g, 0.2cm 3 / g and 0.24cm 3 Preferably, the micropore volume of the modified clay-based material is 0.05-0.4 cm 3 / g, preferably 0.1-0.2cm 3 / g, for example, 0.11 cm 3 / g, 0.13cm 3 / g, 0.15cm 3 / g and 0.16cm 3 / g and other values and the range between any values.
[0036] According to the present invention, the clay-based material can be selected in a wide range. In order to introduce more modifying groups and improve the performance of the modified clay-based material, preferably, the clay-based material is selected from one or more of halloysite, vermiculite, diatomaceous earth, bentonite, montmorillonite and attapulgite, preferably one or more of halloysite, vermiculite, diatomaceous earth and bentonite. Preferably, the mesh number of the clay-based material is 20-100 mesh, preferably 40-80 mesh. Wherein, the form of the halloysite can be halloysite nanotubes.
[0037] A second aspect of the present invention provides a method for preparing a modified clay-based material, the method comprising:
[0038] (1) contacting and reacting a modifier with a clay-based material to obtain a clay-based modified precursor;
[0039] (2) calcining the clay-based modified precursor to obtain a modified clay-based material;
[0040] Wherein, the modifier is selected from one or more structures represented by formula I, formula II and formula III,
[0041]
[0042] wherein A and B are each independently selected from one or more of C1-C12 alkylene and C1-C12 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C12 alkyl, C1-C12 carboxyl, C2-C12 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C12 alkyl, C1-C12 aminoalkyl and C6-C12 aryl, and X - Selected from salt-forming anions.
[0043] According to the present invention, the modified clay-based material prepared by the above method has good pore distribution and abundant active groups. Preferably, the content of the modified groups provided by the modifier in the modified clay-based material is 0.5-30wt%, preferably 5-20wt%, for example, it can be 6wt%, 9wt%, 12wt% and 18wt% and any range between them. Preferably, the mesoporous volume of the modified clay-based material is 0.05-0.5cm 3 / g, preferably 0.15-0.25cm 3 / g, for example, 0.16 cm 3 / g, 0.17cm 3 / g, 0.19cm 3 / g and 0.2cm 3 Preferably, the micropore volume of the modified clay-based material is 0.05-0.4 cm 3 / g, preferably 0.1-0.2cm 3 / g, for example, 0.12 cm 3 / g, 0.13cm 3 / g, 0.15cm 3 / g and 0.2cm 3 / g and other values and the range between any values.
[0044] The modifier and clay-based material of the second aspect of the present invention can be selected and preferably selected from the modifiers and clay-based materials described above, and the present invention will not be described in detail herein.
[0045] According to the present invention, in step (1) of the above method, in order to further obtain the modified clay-based material with better performance by adjusting the amount of modified groups introduced, preferably, the amount of the modifier used is 0.03-0.5g, preferably 0.05-0.3g, relative to 1g of the clay-based material, for example, it can be 0.08g, 0.15g, 0.22g, 0.28g and 0.3g and the range of any values therebetween.
[0046] According to the present invention, in step (1) of the above method, in order to make the modifier and the clay-based material come into contact more fully, the contact reaction can be carried out in the presence of a solvent, and the solvent can be, for example, one or more of water, ethanol, methane, carbon tetrachloride and cyclohexane, preferably water and / or ethanol. Preferably, relative to 1g of the clay-based material, the amount of the solvent is 1-8mL, preferably 3-5mL, for example, 3mL, 3.6mL, 4.5mL and 5mL and any range between the values thereof.
[0047] According to a preferred embodiment of the present invention, in step (1) of the above method, the clay-based material can be acid-treated before the contact reaction. Adsorption materials such as activated carbon, molecular sieves and commercial resins commonly used in the prior art are not only expensive, but also easily affected by the decomposition temperature, resulting in safety risks during use. The clay-based material used in the present invention can be treated with acid to improve the pore structure of the clay-based material, increase the number of silanol and aluminum hydroxyl groups on its micropores and surface, thereby providing more active sites, facilitating the introduction of subsequent modified groups, and can well improve the thermal stability and adsorption effect of the modified clay-based material. In order to improve the effect of the acid treatment and obtain the clay-based material with better performance, preferably, the acid for the acid treatment is selected from one or more of inorganic acids, preferably one or more of hydrochloric acid, sulfuric acid, nitric acid and perchloric acid, and more preferably hydrochloric acid and / or sulfuric acid. Preferably, relative to 1g of the clay-based material, the amount of the acid is 0.05-0.5g, preferably 0.1-0.35g, for example, it can be 0.1g, 0.18g, 0.26g, 0.31g and 0.35g and the range between any values thereof. Preferably, the acid is provided in the form of a solution with a concentration of 0.05-2mol / L, preferably provided in the form of a solution with a concentration of 0.05-1mol / L, for example, it can be 0.05mol / L, 0.25mol / L, 0.62mol / L, 0.85mol / L and 1mol / L and the range between any values thereof. Wherein, the amount of the acid refers to the weight of the acid itself, for example, 6g of the clay-based raw material is treated with 60mL of 0.85mol / L hydrochloric acid, and the amount of hydrochloric acid used is 1.86g. Preferably, the acid treatment time is 2-10 h, preferably 3-5 h, for example, it can be 3 h, 3.5 h, 4 h, 4.5 h, and any value in between.
[0048] According to the present invention, the specific steps of the acid treatment may include: washing and filtering the clay-based material after acid treatment (for example, washing and filtering with a solvent such as water, ethanol, etc. until the pH is neutral), and then performing a first drying treatment to obtain the clay-based material treated with acid. The conditions of the first drying treatment can be selected within a wide range. In order to obtain the clay-based material with better properties, preferably, the temperature of the first drying treatment is 90-150°C, preferably 110-130°C, for example, it can be 110°C, 120°C, 125°C and 130°C and the range between any values thereof. Preferably, the time of the first drying treatment is 5-15h, preferably 6-9h, for example, it can be 6h, 7h, 8h and 9h and the range between any values thereof.
[0049] According to the present invention, the specific steps of step (1) of the above method may include: contacting the modifier with the clay-based material (preferably the clay-based material after acid treatment) in the solvent, washing and filtering (for example, washing and filtering with water, ethanol and other solvents), and then performing a second drying treatment to obtain the clay-based modified precursor. The conditions of each of the above operations can be selected within a wide range. In order to make the effect of the contact reaction better, each condition can be selected. Among them, the operation of the contact reaction may include: ultrasonically mixing the mixture, and then continuously stirring and standing. Preferably, the time of ultrasonic mixing is 0.5-5h, preferably 1-3h, for example, it can be 1h, 1.5h, 2h and 3h and the range between any values thereof. Preferably, the time of continuous stirring is 4-20h, preferably 6-12h, for example, it can be 6h, 8h, 10h and 12h and the range between any values thereof. Preferably, the speed of the continuous stirring is 100-500rpm, preferably 200-400rpm, for example, it can be 200rpm, 250rpm, 300rpm and 350rpm and the range between any values thereof. Preferably, the standing time is 6-20h, preferably 8-12h, for example, it can be 8h, 10h, 11h and 12h and the range between any values thereof. Preferably, the temperature of the second drying treatment is 90-150℃, preferably 110-130℃, for example, it can be 110℃, 120℃, 125℃ and 130℃ and the range between any values thereof. Preferably, the time of the second drying treatment is 5-15h, preferably 6-9h, for example, it can be 6h, 7h, 8h and 9h and the range between any values thereof.
[0050] According to the present invention, in step (2) of the above method, the clay-based modified precursor is subjected to high-temperature calcination treatment, which can make the modified clay-based material have good thermal stability and achieve the purpose of removing impurities and enriching active components. In order to obtain a better calcination effect and further improve the adsorption performance and stability of the modified clay-based material, preferably, the temperature of the calcination treatment is 150-500°C, preferably 200-380°C, for example, it can be 230°C, 280°C, 320°C and 350°C and the range between any values thereof. Preferably, the time of the calcination treatment is 1-6h, preferably 2-4h, for example, it can be 2h, 2.5h, 3h and 4h and the range between any values thereof. Preferably, the heating rate of the calcination treatment is 5-20°C / min, preferably 5-10°C / min, for example, it can be 5°C / min, 7°C / min, 8°C / min and 10°C / min and the range between any values thereof. The starting temperature of the calcination treatment may generally be 20-40°C, and may also be appropriately outside this range. Preferably, the calcination treatment is carried out in the presence of an inactive gas. Preferably, the inactive gas is selected from nitrogen and / or argon. Preferably, the flow rate of the inactive gas is 10-80 mL / min, preferably 20-50 mL / min, for example, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, and any range between these values.
[0051] According to the present invention, the specific steps of step (2) of the above method may include: calcining the clay-based modified precursor, washing to remove ash (for example, washing with water, ethanol or other solvents), and then performing a third drying treatment to obtain the modified clay-based material. The conditions of the third drying treatment can be selected within a wide range. In order to obtain a better modified clay-based material, preferably, the temperature of the third drying treatment is 50-150°C, preferably 70-120°C, for example, it can be 70°C, 80°C, 90°C and 120°C and the range between any values thereof. Preferably, the time of the third drying treatment is 5-20h, preferably 8-12h, for example, it can be 8h, 9h, 10h and 12h and the range between any values thereof.
[0052] The third aspect of the present invention provides a modified clay-based material obtained by the above method.
[0053] A fourth aspect of the present invention provides a use of the modified clay-based material as an adsorbent.
[0054] A fifth aspect of the present invention provides a use of the modified clay-based material as an adsorbent for removing methylchlorosilane impurities in polysilicon production.
[0055] The present invention introduces a modified group provided by a specific modifier into a clay-based material through a specific modifier, thereby increasing the adsorption sites, defect sites and electron cloud density of the micropores and surface of the clay-based material, enhancing its induced polarization ability, and obtaining a modified clay-based material with good performance. The modified clay-based material has excellent adsorption performance, has an adsorption removal rate of more than 80% for methylchlorosilane impurities (monomethyldichlorosilane, monomethyltrichlorosilane), especially has an adsorption removal rate of more than 90% for monomethyldichlorosilane, and has a simple preparation process, low cost and good stability.
[0056] The present invention will be described in detail below through examples.
[0057] In the following examples, the devices used are all conventional experimental devices in the art, the experimental operations adopted are all conventional operations in the art, and the raw materials, reagents, etc. used can be obtained commercially.
[0058] Among them, halloysite nanotubes were purchased from Suzhou Kaifa New Materials Technology Co., Ltd.;
[0059] Bentonite was purchased from Sishui County Yitong Bentonite Co., Ltd.;
[0060] Vermiculite and diatomaceous earth were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0061] 1,5-Diazabicyclo[4.3.0]non-5-ene, 4-carboxybutyltriphenylphosphonium bromide, methyltriphenylphosphonium bromide, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,1,3,3-tetramethylguanidine, allyltributylphosphonium bromide, guanidine hydrochloride, triethanolamine, and tripropyl phosphate were purchased from Merck Reagents.
[0062] Example 1
[0063] (1) Weigh 6 g of 60-mesh halloysite nanotubes, add 60 mL of 0.85 mol / L hydrochloric acid at room temperature for 4 h of acid treatment, wash with water, filter until neutral, and dry at 120° C. for 8 h to obtain acid-treated halloysite nanotubes.
[0064] (2) Weigh 1.5 g of 1,5-diazabicyclo[4.3.0]non-5-ene (i.e., the compound of formula I-1) and dissolve it in 20 ml of water, and mix it with 5 g of the above-mentioned acid-treated halloysite nanotubes by ultrasonic mixing at room temperature for 2 h, and then continue stirring at 300 rpm for 8 h and then stand for 12 h. After washing and filtering the standing mixture with water, it is dried at 120° C. for 8 h to obtain a halloysite nanotube modified precursor.
[0065] (3) The modified halloysite nanotube precursor was placed in a tube furnace under a nitrogen atmosphere for calcination at a nitrogen flow rate of 30 mL / min, and the temperature was raised from room temperature to 280°C at a rate of 5°C / min, and calcined at 280°C for 2 h. After the calcination, the ash was removed by washing with ethanol and water, and dried at 70°C for 12 h to obtain 6.12 g of modified halloysite nanotubes.
[0066] The content of the modified groups provided by the modifier in the modified halloysite nanotubes is 18.3 wt %; the mesopore volume of the modified halloysite nanotubes is 0.2 cm 3 / g, micropore volume is 0.16cm 3 / g. Figure 1 This is the thermal weight loss curve of the modified halloysite nanotubes of this embodiment. It can be seen from the figure that in the range of 20-400°C, the modified halloysite nanotubes have good thermal stability. When used as an adsorbent, it can effectively inhibit thermal decomposition caused by local temperature rise during the process.
[0067] Example 2
[0068] (1) Weigh 6 g of 80-mesh bentonite, add 60 mL of 0.85 mol / L hydrochloric acid at room temperature for 4 h of acid treatment, wash with water, filter until neutral, and dry at 120° C. for 8 h to obtain acid-treated bentonite.
[0069] (2) Weigh 1 g of 4-carboxybutyltriphenylphosphonium bromide (i.e., the compound shown in Formula II-2) and dissolve it in 20 ml of water, and mix it with 5 g of the above-mentioned acid-treated bentonite by ultrasonic mixing at room temperature for 1 hour, and then continue stirring at 200 rpm for 12 hours and then stand for 8 hours. After washing and filtering the standing mixture with water, it is dried at 120°C for 8 hours to obtain a bentonite modified precursor.
[0070] (3) The bentonite modified precursor was placed in a tubular furnace under a nitrogen atmosphere for calcination, with a nitrogen flow rate of 50 mL / min, and the temperature was raised from room temperature to 320°C at a rate of 5°C / min, and calcined at 320°C for 4 h. After calcination, the ash was removed by washing with ethanol and water, and dried at 120°C for 8 h to obtain 5.73 g of modified bentonite.
[0071] The content of modified groups provided by the modifier in the modified bentonite is 12.7wt%; the mesopore volume of the modified bentonite is 0.18cm 3 / g, micropore volume is 0.13cm 3 / g.
[0072] Example 3
[0073] (1) Weigh 6 g of 70-mesh halloysite nanotubes, add 60 mL of 0.85 mol / L hydrochloric acid at room temperature for 4 h of acid treatment, wash with water, filter until neutral, and dry at 120° C. for 8 h to obtain acid-treated halloysite nanotubes.
[0074] (2) Weigh 0.5 g of methyl triphenylphosphonium bromide (i.e., the compound of formula II-1) and dissolve it in 20 ml of water, and mix it with 5 g of the above-mentioned acid-treated halloysite nanotubes by ultrasonic mixing at room temperature for 3 hours, and then continue stirring at 400 rpm for 6 hours and then stand for 12 hours. After washing and filtering the standing mixture with water, it is dried at 120° C. for 8 hours to obtain a modified halloysite nanotube precursor.
[0075] (3) The modified halloysite nanotube precursor was placed in a tube furnace under a nitrogen atmosphere for calcination at a nitrogen flow rate of 40 mL / min, and the temperature was increased from room temperature to 350°C at a rate of 10°C / min, and calcined at 350°C for 2 h. After calcination, the ash was removed by washing with ethanol and water, and dried at 90°C for 8 h to obtain 5.38 g of modified halloysite nanotubes.
[0076] The content of the modified groups provided by the modifier in the modified halloysite nanotubes is 7.1 wt %; the mesopore volume of the modified halloysite nanotubes is 0.19 cm 3 / g, micropore volume is 0.15cm 3 / g.
[0077] Example 4
[0078] (1) Weigh 6 g of 60-mesh diatomaceous earth, add 60 mL of 0.85 mol / L hydrochloric acid at room temperature for 4 h of acid treatment, wash with water, filter until neutral, and dry at 120° C. for 8 h to obtain acid-treated diatomaceous earth.
[0079] (2) Weigh 1.2 g of 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (i.e., the compound of formula I-2) and dissolve it in 20 ml of water, and mix it with 5 g of the above-mentioned acid-treated diatomaceous earth by ultrasonic mixing at room temperature for 2 hours, and then continue stirring at 300 rpm for 6 hours and then stand for 10 hours. After washing and filtering the standing mixture with water, it is dried at 100° C. for 8 hours to obtain a diatomaceous earth modified precursor.
[0080] (3) The diatomite modified precursor was placed in a tubular furnace under a nitrogen atmosphere for calcination, with a nitrogen flow rate of 20 mL / min, and the temperature was increased from room temperature to 350°C at a rate of 10°C / min, and calcined at 350°C for 2 h. After the calcination, the ash was removed by washing with ethanol and water, and dried at 120°C for 8 h to obtain 5.36 g of modified diatomite.
[0081] The content of modified groups provided by the modifier in the modified diatomite is 6.7wt%; the mesopore volume of the modified diatomite is 0.17cm 3 / g, micropore volume is 0.13cm 3 / g.
[0082] Example 5
[0083] (1) Weigh 6 g of 60-mesh vermiculite, add 60 mL of 0.85 mol / L hydrochloric acid at room temperature for 4 h of acid treatment, wash with water, filter until neutral, and dry at 120° C. for 8 h to obtain acid-treated vermiculite.
[0084] (2) Weigh 1.5 g of 1,1,3,3-tetramethylguanidine (i.e., the compound represented by Formula III-1) and dissolve it in 20 ml of water, and mix it with 5 g of the above-mentioned acid-treated vermiculite by ultrasonication at room temperature for 2 h, and then continue stirring at 300 rpm for 8 h and then stand for 12 h. After washing and filtering the standing mixture with water, dry it at 120° C. for 8 h to obtain a vermiculite-modified precursor.
[0085] (3) The vermiculite-modified precursor was placed in a tubular furnace under a nitrogen atmosphere for calcination, with a nitrogen flow rate of 30 mL / min, and the temperature was raised from room temperature to 370°C at a rate of 10°C / min, and calcined at 370°C for 3 h. After calcination, the ash was removed by washing with ethanol and water, and dried at 90°C for 8 h to obtain 5.52 g of modified vermiculite.
[0086] The content of modified groups provided by the modifier in the modified vermiculite is 9.4wt%; the mesopore volume of the modified vermiculite is 0.19cm 3 / g, micropore volume is 0.15cm 3 / g.
[0087] Example 6
[0088] The method described in Example 1 is different in that in step (2), 1.5 g of 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (i.e., the compound represented by formula I-2) is used instead of 1,5-diazabicyclo[4.3.0]non-5-ene to obtain 6.1 g of modified halloysite nanotubes.
[0089] The content of the modified groups provided by the modifier in the modified halloysite nanotubes is 18 wt %; the mesopore volume of the modified halloysite nanotubes is 0.18 cm 3 / g, micropore volume is 0.15cm 3 / g.
[0090] Example 7
[0091] The method of Example 1 is different in that step (1) is not performed, i.e. the halloysite nanotubes are not subjected to acid treatment. Instead, commercially available 60-mesh halloysite nanotubes are directly used to replace the acid-treated halloysite nanotubes for modification in step (2), and finally 5.26 g of modified halloysite nanotubes are obtained.
[0092] The content of the modified groups provided by the modifier in the modified halloysite nanotubes is 4.9 wt %; the mesopore volume of the modified halloysite nanotubes is 0.13 cm 3 / g, micropore volume is 0.09cm 3 / g.
[0093] Example 8
[0094] The method of Example 1 is different in that the amount of the modifier 1,5-diazabicyclo[4.3.0]non-5-ene used in step (2) is 3 g, and modified halloysite nanotubes are finally obtained.
[0095] The content of the modified groups provided by the modifying agent in the modified halloysite nanotubes is 27 wt %.
[0096] Example 9
[0097] According to the method of Example 1, the difference is that the amount of the modifier 1,5-diazabicyclo[4.3.0]non-5-ene used in step (2) is 0.2 g, and finally modified halloysite nanotubes are obtained.
[0098] The content of the modified groups provided by the modifying agent in the modified halloysite nanotubes is 3 wt %.
[0099] Example 10
[0100] The method of Example 1 is different in that in step (2), the modifier 1,5-diazabicyclo[4.3.0]non-5-ene is replaced by an equal weight of allyltributylphosphonium bromide to finally obtain modified halloysite nanotubes.
[0101] The content of modified groups provided by the modifying agent in the modified halloysite nanotubes is 16.9 wt %.
[0102] Embodiment 11
[0103] The method of Example 1 is different in that in step (2), the modifier 1,5-diazabicyclo[4.3.0]non-5-ene is replaced by an equal weight of guanidine hydrochloride to finally obtain modified halloysite nanotubes.
[0104] The content of the modified groups provided by the modifying agent in the modified halloysite nanotubes is 16.7 wt %.
[0105] Comparative Example 1
[0106] Halloysite nanotubes were directly used as adsorbents, and their mesopore volume was 0.11 cm 3 / g, micropore volume is 0.07cm 3 / g.
[0107] Comparative Example 2
[0108] The method of Example 1 is different from that of Example 1, in which only the acid treatment of step (1) is performed on the halloysite nanotubes. The mesoporous volume of the acid-treated halloysite nanotubes is 0.19 cm 3 / g, micropore volume is 0.15cm 3 / g.
[0109] Comparative Example 3
[0110] The method of Example 1 is different in that in step (2), the modifier 1,5-diazabicyclo[4.3.0]non-5-ene is replaced by an equal weight of triethanolamine to finally obtain modified halloysite nanotubes.
[0111] Comparative Example 4
[0112] The method of Example 1 is different in that in step (2), the modifier 1,5-diazabicyclo[4.3.0]non-5-ene is replaced by an equal weight of tripropyl phosphate to finally obtain modified halloysite nanotubes.
[0113] Test Case
[0114] 30 ml of crude distilled trichlorosilane (carbon impurity concentration is shown in Table 1) was taken respectively, and 2 g of the adsorbent prepared in Examples 1-11 and Comparative Examples 1-4 was added thereto respectively. Static adsorption was carried out for 30 min at room temperature. The supernatant was taken and the contents of monomethyldichlorosilane and monomethyltrichlorosilane in the supernatant were tested by GC-MS. The results are shown in Table 1.
[0115] Table 1
[0116]
[0117]
[0118] It can be seen from Table 1 that the adsorbents prepared by Examples 1-11 of the technical solution of the present invention have much better adsorption removal rates for methylchlorosilane impurities than Comparative Examples 1-4, and some preferred embodiments have an adsorption removal rate of more than 90% for monomethyldichlorosilane and an adsorption removal rate of more than 80% for monomethyltrichlorosilane. It can be seen that the modified clay-based material of the present invention can be used as an adsorbent to well remove methylchlorosilane impurities in trichlorosilane.
[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A modified clay-based material, characterized in that: The modified clay-based material is obtained by modifying the clay-based material with a modifier, wherein the modifier is selected from one or more structures represented by formula I, formula II and formula III. wherein A and B are each independently selected from one or more of C1-C12 alkylene and C1-C12 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C12 alkyl, C1-C12 carboxyl, C2-C12 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C12 alkyl, C1-C12 aminoalkyl and C6-C12 aryl, and X - Selected from salt-forming anions.
2. The modified clay-based material according to claim 1, wherein A and B are each independently selected from one or more of C1-C6 alkylene and C1-C6 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C6 alkyl, C1-C6 carboxyl, C2-C6 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C6 alkyl, C1-C6 aminoalkyl and C6-C12 aryl, X - Selected from Cl - Br - ,I - 、CH3COO - 、NO3 - 、HSO4 - 、H2PO4 - 、BF4 - and SbF6 - One or more of; Preferably, A and B are each independently selected from one or more of methylene, ethylene, n-propylene, n-butylene, n-pentylene, n-hexylene, -NHCH2CH2-, -CH2NHCH2-, -NHCH2CH2CH2-, -CH2NHCH2CH2-, -NHCH2CH2CH2CH2-, -NH(CH3)CH2CH2CH2-, -CH2NHCH2CH2CH2-, -CH2CH2NHCH2CH2- and -NHCH2CH2CH2CH2CH2-, and R1, R2, R3 and R4 are each independently selected from methyl, ethyl, n-propyl, isopropyl R5, R6, R7 and R8 are each independently selected from one or more of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, carboxymethyl, carboxyethyl, n-carboxypropyl, n-carboxybutyl, n-carboxypentyl, vinyl, allyl, 1-butenyl, 2-butenyl, phenyl, benzyl, p-methylphenyl, p-ethylphenyl, p-n-propylphenyl and naphthyl, R5, R6, R7 and R8 are each independently selected from one or more of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, aminomethyl, aminoethyl, n-aminopropyl, isoaminopropyl, n-aminobutyl, isoaminobutyl, n-aminopentyl, n-aminohexyl, phenyl, benzyl, p-methylphenyl, p-ethylphenyl, p-n-propylphenyl and naphthyl, X - Selected from Cl - Br - and I - One or more of; More preferably, the modifier is selected from one or more compounds represented by the following structures: More preferably, the modifier is selected from one or more compounds represented by the following structures:
3. The modified clay-based material according to claim 1 or 2, wherein: The content of the modified groups provided by the modifier in the modified clay-based material is 0.5-30wt%, preferably 5-20wt%; Preferably, the mesopore volume of the modified clay-based material is 0.05-0.5 cm 3 / g, preferably 0.15-0.25cm 3 / g; Preferably, the micropore volume of the modified clay-based material is 0.05-0.4 cm 3 / g, preferably 0.1-0.2cm 3 / g.
4. The modified clay-based material according to any one of claims 1 to 3, wherein: The clay-based material is selected from one or more of halloysite, vermiculite, diatomaceous earth, bentonite, montmorillonite and attapulgite, preferably one or more of halloysite, vermiculite, diatomaceous earth and bentonite; Preferably, the mesh size of the clay-based material is 20-100 mesh, preferably 40-80 mesh.
5. A method for preparing a modified clay-based material, characterized in that: The method includes: (1) contacting and reacting a modifier with a clay-based material to obtain a clay-based modified precursor; (2) calcining the clay-based modified precursor to obtain a modified clay-based material; Wherein, the modifier is selected from one or more structures represented by formula I, formula II and formula III, wherein A and B are each independently selected from one or more of C1-C12 alkylene and C1-C12 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C12 alkyl, C1-C12 carboxyl, C2-C12 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C12 alkyl, C1-C12 aminoalkyl and C6-C12 aryl, and X - Selected from salt-forming anions.
6. The method according to claim 5, wherein: Relative to 1g of the clay-based material, the amount of the modifier is 0.03-0.5g, preferably 0.05-0.3g; Preferably, the content of the modified groups provided by the modifier in the modified clay-based material is 0.5-30wt%, preferably 5-20wt%; Preferably, the mesopore volume of the modified clay-based material is 0.05-0.5 cm 3 / g, preferably 0.15-0.25cm 3 / g; Preferably, the micropore volume of the modified clay-based material is 0.05-0.4 cm 3 / g, preferably 0.1-0.2cm 3 / g.
7. The method according to claim 5 or 6, wherein: A and B are each independently selected from one or more of C1-C6 alkylene and C1-C6 aminoalkylene, R1, R2, R3 and R4 are each independently selected from one or more of C1-C6 alkyl, C1-C6 carboxyl, C2-C6 alkenyl and C6-C12 aryl, R5, R6, R7 and R8 are each independently selected from one or more of H, C1-C6 alkyl, C1-C6 aminoalkyl and C6-C12 aryl, X - Selected from Cl - Br - ,I - 、CH3COO - 、NO3 - 、HSO4 - 、H2PO4 - 、BF4 - and SbF6 - One or more of; Preferably, A and B are each independently selected from one or more of methylene, ethylene, n-propylene, n-butylene, n-pentylene, n-hexylene, -NHCH2CH2-, -CH2NHCH2-, -NHCH2CH2CH2-, -CH2NHCH2CH2-, -NHCH2CH2CH2CH2-, -NH(CH3)CH2CH2CH2-, -CH2NHCH2CH2CH2-, -CH2CH2NHCH2CH2- and -NHCH2CH2CH2CH2CH2-, and R1, R2, R3 and R4 are each independently selected from methyl, ethyl, n-propyl, isopropyl R5, R6, R7 and R8 are each independently selected from one or more of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, carboxymethyl, carboxyethyl, n-carboxypropyl, n-carboxybutyl, n-carboxypentyl, vinyl, allyl, 1-butenyl, 2-butenyl, phenyl, benzyl, p-methylphenyl, p-ethylphenyl, p-n-propylphenyl and naphthyl, R5, R6, R7 and R8 are each independently selected from one or more of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, aminomethyl, aminoethyl, n-aminopropyl, isoaminopropyl, n-aminobutyl, isoaminobutyl, n-aminopentyl, n-aminohexyl, phenyl, benzyl, p-methylphenyl, p-ethylphenyl, p-n-propylphenyl and naphthyl, X - Selected from Cl - Br - and I - One or more of; More preferably, the modifier is selected from one or more compounds represented by the following structures: More preferably, the modifier is selected from one or more compounds represented by the following structures:
8. The method according to any one of claims 5 to 7, wherein: The clay-based material is selected from one or more of halloysite, vermiculite, diatomaceous earth, bentonite, montmorillonite and attapulgite, preferably one or more of halloysite, vermiculite, diatomaceous earth and bentonite; Preferably, the mesh size of the clay-based material is 20-100 mesh, preferably 40-80 mesh.
9. The method according to any one of claims 5 to 8, wherein the solvent for the contact reaction is selected from one or more of water, ethanol, methane, carbon tetrachloride and cyclohexane, preferably water and / or ethanol; Preferably, the amount of the solvent used is 1-8 mL, preferably 3-5 mL, relative to 1 g of the clay-based material.
10. The method according to any one of claims 5 to 9, wherein: In step (1), before the contact reaction, the clay-based material is first subjected to an acid treatment; Preferably, the acid for the acid treatment is selected from one or more inorganic acids, preferably one or more of hydrochloric acid, sulfuric acid, nitric acid and perchloric acid, more preferably hydrochloric acid and / or sulfuric acid; Preferably, the amount of the acid is 0.05-0.5 g, preferably 0.1-0.35 g, relative to 1 g of the clay-based material; Preferably, the acid is provided in the form of a solution having a concentration of 0.05-2 mol / L, preferably in the form of a solution having a concentration of 0.05-1 mol / L.
11. The method according to any one of claims 5 to 10, wherein: The calcination temperature is 150-500°C, preferably 200-380°C; Preferably, the calcination treatment time is 1-6h, preferably 2-4h; Preferably, the heating rate of the calcination treatment is 5-20°C / min, preferably 5-10°C / min.
12. A modified clay-based material obtained by the method according to any one of claims 5 to 11.
13. Use of the modified clay-based material according to any one of claims 1 to 4 and 12 as an adsorbent.
14. Use of the modified clay-based material according to any one of claims 1 to 4 and 12 as an adsorbent for removing methylchlorosilane impurities in polysilicon production.
